Efektivitas Pendidikan Kesehatan Menggunakan Media Video Animasi terhadap Pengetahuan Remaja Putri tentang Nyeri Haid (Dismenore) pada Siswi di SMPN 8 Cimahi Tahun 2025 - Salmah Amaliyah; Rani Sumarni; Yuswandi Yuswandi (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2026)
Background: Dysmenorrhea is a reproductive health issue commonly experienced by adolescent girls and can interfere with their academic activities. Enhancing knowledge through engaging health education media, such as animated videos, is believed to be effective because it aligns with the characteristics of adolescents. Objective: To determine the effectiveness of health education using animated video media on adolescent girls’ knowledge of dysmenorrhea at SMPN 8 Cimahi in 2025. Method: Pre-experimental with a one-group pre-test post-test design. The study population consisted of all eighth-grade adolescent girls; quota sampling was used to select 68 female students. The instrument was a questionnaire assessing the effectiveness of animated video health education media. The animated video lasted 3 minutes and 30 seconds. The research data comprised primary data obtained through pre- and post-intervention knowledge questionnaires administered to the respondents. Data analysis was performed univariately to examine frequency distributions with percentages, and bivariately using the Wilcoxon test and the Marginal Homogeneity test. Results: Before the intervention using animated videos, of the 68 adolescent girls, the majority had adequate knowledge (60.3%), 33.8% had good knowledge, and 5.9% had insufficient knowledge. After the intervention, knowledge levels increased, with no respondents falling into the insufficient category; 97.1% were in the adequate category and 2.9% in the good category. The Wilcoxon test showed p = 0.772 (p > 0.05), while the Marginal Homogeneity test showed p = 0.002 (p < 0.05), indicating a significant difference in knowledge before and after the intervention. Conclusion: Health education using animated video media is effective in improving adolescent girls’ knowledge about menstrual pain (dysmenorrhea).